Five concomitant polymorphs of a green fluorescent protein chromophore (GFPc) analogue: understanding variations in photoluminescence with pi-stacking interactions - Mali, Bhupendra P.; Dash, Soumya Ranjan; Nikam, Shrikant B.; Puthuvakkal, Anisha; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Acta Crystallographica Section B-Structural Science Crystal Engineering and Materials, 2020)
The synthetically modified green fluorescent protein chromophore analogue 3,4,5-trimethoxybenzylidene imidazolinone (1) yielded five polymorphs (I, II, III, IV, V) concomitantly irrespective of the solvent used for crystallization. The pentamorphic modification of 1 is solely due to the interplay of iso-energetic weak intermolecular interactions in molecular associations as well as the conformational flexibility offered by a C-C single bond, which connects the electron-deficient moiety imidazolinone with the electron-rich trimethoxybenzylidene group. A common structural feature observed in all the polymorphs is the formation of a `zero-dimensional' centrosymmetric dimeric unit through a short and linear C-H center dot center dot center dot O hydrogen bond engaging phenyl C-H and imidazolinone carbonyl oxygen. However, the networking of these dimeric units showed a subtle difference in all the polymorphs. The 2D isostructurality was observed between polymorphs I, II and III, while the other two polymorphs IV and V revealed only `zero-dimensional' isostructurality. The different fluorescence emissions of Form I (blue) and Forms II to V (yellow) were attributed to the differences in pi-stacking interactions. It shows that one can modulate the photophysical properties of these smart materials by slightly altering their crystal structure. Such an approach will aid in developing new multi-colour organic fluorescent materials of varying crystal structures for live-cell imaging and fluorescent sensing applications.
Keywords: green fluorescent protein; hydrogen bonds; isostructurality; photoluminescence; pi-stacking; Polymorphs

Lead-free zero dimensional tellurium(iv) chloride-organic hybrid with strong room temperature emission as a luminescent material - Biswas, Anupam; Bakthavatsalam, Rangarajan; Bahadur, Vir; Biswas, Chinmoy; Mali, Bhupendra P.; Raavi, Sai Santosh Kumar; Gonnade, Rajesh G.; Kundu, Janardan (Journal of Materials Chemistry C, 2021)
Despite the current progress in `Pb-free' low dimensional main group metal halide based luminescent materials, it is challenging to synthesize Te(iv) halide hybrids with strong ambient emission with excitation features in the visible range as efficient and stable phosphors for potential lighting applications. Reported here is a (benzyltriethylammonium)(2)TeCl6 zero dimensional hybrid material with excitation features in the visible range and strong room temperature, broadband, intrinsic luminescence (PLQY similar to 15%) arising due to self-trapped excitons (STEs). Furthermore, a proof-of-concept LED architecture demonstrates successful optical down-conversion with a visible light excitation source. Here, exclusive adoption of a `regular' octahedral Te(iv)-halide unit structure with minimal static distortion provides a unique opportunity to unmask the role played by 5s(2) lone pair electrons in shaping the emissive properties. This effort may open up new avenues towards unravelling the role of lone pair stereoactivity in controlling the PLQY in low dimensional hybrids that has proven to be challenging for the reported (Sb, Sn) based low dimensional 5s(2) metal halide hybrid materials.

Metal halide structure and the extent of distortion control the photo-physical properties of luminescent zero dimensional organic-antimony(iii) halide hybrids - Biswas, Anupam; Bakthavatsalam, Rangarajan; Mali, Bhupendra P.; Bahadur, Vir; Biswas, Chinmoy; Raavi, Sai Santosh Kumar; Gonnade, Rajesh G.; Kundu, Janardan (Journal of Materials Chemistry C, 2021)
Antimony(iii) halide based zero dimensional hybrids have gained attention as broadband emitters. Until now, quadrangular pyramidal SbX5 based and octahedral SbX6 based 0D hybrids have been reported utilizing different organic ligands demonstrating some structural tunability affecting their emissive properties. Utilizing a common organic ligand, here we demonstrate the structural tunability (quadrangular pyramidal, octahedral, or a combination thereof) of the metal halide unit in Sb(iii)Cl 0D hybrids with contrasting photo-physical properties (broadband, Stokes shift, strong/weak colored emission). The structure-property-mechanism correlation of the synthesized compounds [1 (C12H52Cl18N8O4Sb3; tris Sb green); 2 (C12H50Cl14N8O3Sb2; tris Sb red); 3 (C24H88Cl25N16O4Sb3; tris Sb yellow)] identifies crucial factors that control their emissive properties. The X-ray analysis reveals the structure (1-octahedral; 2-quadrangular pyramidal; 3-combination thereof) and the order of the extent of structural distortion as 1-3 MUCH LESS-THAN 2. The metal halide coordination environment asymmetry and its structure are observed to dictate PL emission energy (1-green; 2-red; 3-yellow) as supported by a qualitative Molecular Orbital scheme. The extent of structural distortion guides the observed Stokes shifts (1-165 nm; 2-290 nm; 3-200 nm; 1-3 < 2). Interestingly, the extent of distortion is found to be well correlated with the observed PLQY (1-45%; 2-6%; 3-43%; 1-3 >> 2). This report clearly demonstrates the structural tunability and the effect of the metal halide unit structure/distortion in shaping the emissive properties of 0D organic Sb(iii) halide hybrids.

Synergistic electronic coupling/cross-talk between the isolated metal halide units of zero dimensional heterometallic (Sb, Mn) halide hybrid with enhanced emission - Biswas, Anupam; Bakthavatsalam, Rangarajan; Das, Deep K.; Sam, Jisvin; Mali, Bhupendra P.; Biswas, Chinmoy; Maana, Narugopal; Thomson, Stuart; Raavi, Sai Santosh Kumar; Kurungot, Sreekumar; Gonnade, Rajesh G.; Dutta, Sudipta; et al. (Journal of Materials Chemistry C, 2021)
Heterometallic 0D metal halide hybrids, consisting of more than one kind of metal halide units, are anticipated to manifest synergistic effects on the photo-physical properties of the constituent metal halide units. Such architectures hold great promise for design and development of function-targeted materials. However, heterometallic 0D hybrids, featuring isolated metal halide units, typically do not show any synergistic effects due to large inter-unit spatial separations that inhibit interactions/coupling between the constituent metal halide units. It remains challenging to design synthetic strategies that would support structural modifications to allow synergistic electronic coupling between the metal halide units in heterometallic 0D hybrids. Here, we report synthesis and characterization of heterometallic (Sb, Mn) 0D hybrid, namely Tris SbMnCl, with isolated MnCl5 units, (Sb/Mn)Cl-6 units, dispersed in the organic ligand matrix and layer of dynamic and networked water molecules. Steady state and time resolved emission spectra (TRES) analysis suggests strong synergistic interaction between the isolated metal halide units. Efficient energy transfer from the strongly absorbing Sb centres to emissive Mn centres results in the observed enhanced emission. Proton conductivity measurements together with first-principles calculations suggest the unique role of the networked water molecules in mediating the electronic coupling/energy transfer between the separated metal halide units in Tris SbMnCl hybrid. This report highlights the role of structure/composition of the synthesized heterometallic 0D hybrid in attaining electronic dimensionality higher than 0D through synergistic electronic interaction between the isolated metal halide units.

Controlled modulation of the structure and luminescence properties of zero-dimensional manganese halide hybrids through structure-directing metal-ion (Cd2+ and Zn2+) centers - Das, Deep Kumar; Bakthavatsalam, Rangarajan; Anilkumar, Vishnu; Mali, Bhupendra P.; Ahmed, Md Soif; Raavi, Sai Santosh Kumar; Pallepogu, Raghavaiah; Kundu, Janardan (Inorganic Chemistry, 2022)
Zero-dimensional (0D) metal halide hybrids with high exciton binding energy are excellent materials for lighting applications. Controlling/modulating the structure of the con-stituent metal halide units allows tunability of their photo-luminescence properties. 0D manganese halide hybrids are currently attracting research efforts in lighting applications due to their eco-friendly and strong emission. However, structural transformation-induced tunability of their photophysical propertieshas rarely been reported. Herein, we demonstrate a rationalsynthetic strategy to modulate the structure and luminescenceproperties of 0D Mn(II) halide hybrids utilizing the structure-directing d10metal ions (Cd2+/Zn2+). 0D metal halide hybrids ofCd2+/Zn2+, which act as hosts with tunable structures, accept Mn2+ions as substitutional dopants. This structural flexibility of thehost d10metal ions is realized by optimizing the metal-to-ligand ratio (Cd/AEPip). This reaction parameter allows structuraltransformation from an octahedral (AEPipCdMnBrOh) to a tetrahedral (AEPipCdMnBrTd) 0D Mn halide hybrid with tunableluminescence (orange -> green) with high photoluminescence quantum yield. Interestingly, when Zn2+is utilized, a tetrahedralAEPipZnMnBr structure forms exclusively with strong green emission. Optical and single-crystal X-ray diffraction structural analysisof the host and the doped system supports our experimental data and confirms the structure-directing role played by Cd2+/Zn2+centers. This work demonstrates a rational strategy to modulate the structure/luminescence properties of 0D Mn(II) halide hybrids, which can further be implemented for other 0D metal halide hybrids

Polymorphs of green fluorescence protein chromophore analogue: fluorescence switching with thermal stimuli - Mali, Bhupendra P.; Dash, Soumya Ranjan; Biswas, Anupam; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Crystal Growth & Design, 2022)
Polymorphs of fluorescent organic materials offer significant implications in optoelectronics and advanced materials as they modulate photoluminescence properties. A slight alteration in the conformation/packing of molecules in the crystals shows variation in photoluminescence. This necessitates the polymorph screening of these materials to develop novel crystalline forms with distinct fluorescence emissions for broader application. In continuation of our work on the polymorph screening of Green Fluorescence Protein Chromophore (GFPc), we have synthesized a new imidazoline derivative, ethyl (Z)-2-(2-methyl-5-oxo-4-(3,4,5-trimethoxybenzylidene)-4,5-dihydro-1H-imi dazol-1- yl)acetate (1). Polymorph screening of 1 under different crystallization conditions revealed three polymorphs, Form I (needle), Form II (block), and Form III (polycrystalline material). Forms I and II are the outcome of solution crystallization, whereas Form III was produced from the melt crystallization of Forms I and II. DSC, HSM, and powder and single-crystal XRD studies indicate the conversion of Form I and Form III crystals to Form II crystals on thermal stimuli. The photoluminescence studies revealed cyan, yellow, and yellowish-green fluorescence emission for Forms I, II, and III crystals, respectively. The difference in photoluminescence could be due to the variance in aggregation modes like H-aggregation in Form I and J-aggregation in Form II crystals. Form I, Form II, and Form III crystals also showed irreversible thermal fluorescent switching from cyan-yellow-green due to polymorphic phase transitions. The study correlates the direct observation of the modulation of the excited-state transition under thermal stimuli in the crystalline phase. It will help augment the pace in the research of thermally responsive fluorescent materials.

Cocrystal approach to modulate the photoluminescent properties of a GFP chromophore analogue: role of halogen/hydrogen bonding in achieving a wide range of solid-state fluorescence emissions - Mali, Bhupendra P.; Dash, Soumya Ranjan; Annadhasan, Mari; Biswas, Anupam; Manoj, Kochunnoonny; Vanka, Kumar; Gonnade, Rajesh G. (Crystal Growth & Design, 2023)
Fine-tuning the photophysical properties of fluorescentorganicsolids is essential to attain multicolor displays and meet the demandfor futuristic light-emitting materials. Here, we report the tunableluminescence of a green fluorescent protein (GFP) chromophore analogue,3,4,5-TIA (A), based on the formation of two-component molecular cocrystalswith six different coformers. Coformers selected to synthesize thebinary cocrystals include 1,4-diiodotetrafluorobenzene (B), perfluoronaphthalene(C), 1,4-dibromotetrafluorobenzene (D), 2,3,5,6-tetrafluoroterephthalicacid (E), benzene-1,2,4,5-tetracarbonitrile (F), and benzene-1,2,4,5-tetracarboxylicacid (G). Interestingly, the cocrystals A center dot C and A center dot Fshowed molecular crystal polymorphism with a slight variation in fluorescence,revealing an aggregation-induced emission (AIE). A crystal structureanalysis showed the interplay of hydrogen bonding, halogen bonding,and aromatic pi-stacking interactions in associating neutralsolid components in the cocrystal. All of the novel cocrystals displayeda wide range of photoluminescence ranging from blue to dark orange.The time-dependent density functional theory (TD-DFT) calculationsindicate the changes in the energy level structures (HOMO to LUMO)in cocrystals that resulted in variations in fluorescence emission.The study aims to further understand the structure-propertyrelationship between molecular arrangement and photoluminescence. Cocrystals of a GFPc analogue with differentcoformers displayeda wide range of fluorescence emissions ranging from blue to dark orangewith varying quantum yields. With similar geometries of pi-stackinginteractions, hydrogen and halogen bonding have played a vital rolein fine-tuning the photoluminescence; halogen bonding leads to a blueshift, and hydrogen bonding results in a red shift.

Organocatalysed one-pot three component synthesis of 3,3′-disubstituted oxindoles featuring an all-carbon quaternary center and [spiro 2H-pyran-3,4′-indoline] - Nichinde, Chandrakant B.; Patil, Baliram R.; Chaudhari, Suryakant S.; Mali, Bhupendra P.; Gonnade, Rajesh G.; Kinage, Anil K. (RSC Advances, 2023)
A simple and efficient methodology for the one-pot synthesis of 3,3 `-disubstituted oxindoles featuring an all-carbon quaternary center has been demonstrated through l-proline catalysed three-component reaction based on sequential Knoevenagel condensation/Michael addition and also one-pot synthesis of spiro[2H-pyran-3,4 `-indoline] through consecutive Knoevenagel condensation/Michael addition/reduction/cyclization reactions from readily available isatin derivatives, malononitrile, and ketones. The present methodology presents several advantages, including simple reaction set-up, short reaction times, and easy to work-up. Also, this strategy offers broad substrate scope with excellent yields and high atom economy, under mild reaction conditions.

Zwitterionic tetrastanna(II) cyclic crown - Sahoo, Padmini; Chibde, Purva; Das, Satyabrata; Banerjee, Subhrashis; Mali, Bhupendra P.; Vanka, Kumar; Gonnade, Rajesh G.; Yildiz, Cem. B.; Majumdar, Moumita (European Journal of Inorganic Chemistry, 2023)
A 12-membered zwitterionic tetrastanna(II) cycle 1 having a crown ether-like topology has been isolated from the deprotonation of 1,1 & PRIME;-methylenediimidazole (B) with two equivalents of Sn[N(SiMe3)(2)](2) (A). The solid-state structure and NMR analysis confirms the tetrastanna(II) cycle 1 to be comprised of two stannate(II) and two stannyliumylidene ion pairs in alternating positions of the heterocycle. Computational analysis shows greater nucleophilicity at the proximally located stannate(II) centers. Nonetheless, the tetrastanna(II) cycle 1 remains poorly reactive due to engagement of Sn-II lone pair electrons in intramolecular donor-acceptor interactions. Simple deprotonation reaction between Sn[N(SiMe3)(2)](2) (A) and N-(diisopropylphenyl)imidazole (C) in equimolar ratio has led to a stannylene 2, involving the formation of a Sn-C covalent bond with the anionic imidazol-2-yl carbon center along with the release of NH(SiMe3)(2). Compound 2 exists as a dimer, where the unsubstituted ring nitrogen atom coordinated intermolecularly to the other stannylene center.
Keywords: Deprotonation; Imidazole; Macrocycle; Sn-II cation; stannylene

Brønsted acid- and Ni(ii)-catalyzed C-H oxidation/rearrangement of cyclotriveratrylenes (CTVs) to cyclic and acyclic quinones as potential anti-cancer agents - Darole, Ratanamala S.; Choudhary, Shailendra Singh; Sharma, Himanshu; Mali, Bhupendra P.; Gopu, Booblan; Vanka, Kumar; Senthilkumar, Beeran (Organic and biomolecular chemistry, 2024)
This paper describes a simple and practical protocol for the direct synthesis of acyclic and cyclic quinone derivatives via an acid-promoted nickel(ii)-catalyzed inner rim C-H oxidation of cyclotriveratrylene (CTV) and its analogues. The cyclic quinone derivatives resulted from trimethoxy-cyclotriveratrylene (TCTV) through C-C bond formation via intramolecular ipso substitution followed by subsequent anionic rearrangement containing stereo-vicinal quaternary centers. The DFT calculations strongly support the experimental findings and reveal the role of Bronsted acids in the C-H bond activation of CTV. All the newly synthesized compounds were screened for their in vitro anti-cancer activity using colorimetric SRB assay analysis. Among them, compounds 3a, 3d, 3h, 4a, 4b, 4c and 4e exhibited moderate anticancer activity against A549, HCT-116, PC-3, MDA-MB-231, HEK-293 and SW620 human cancer cell lines.

Unravelling polymorphism-driven luminescence in GFP chromophore analogues: insights into the phase transition and morphology-dependent optical waveguide properties - Dabke, Niteen B.; Raut, Yash; Mali, Bhupendra P.; Pandya, Rinu; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Journal of Materials Chemistry C, 2024)
The advent of multi-emission organic solid-state materials in response to external stimuli has sparked the scientific community due to their potential application in developing sophisticated optoelectronic sensors and bioanalytical tools. This article presents green fluorescent protein chromophore (GFPc) analogue-based polymorphs exhibiting significantly different emissions due to various noncovalent interactions in the supramolecular environment and conformational alterations in the crystalline state. In both compounds (A and B), the polymorphs undergo monotropic thermal phase transitions that are characterized by DSC, HSM, and VT-PXRD techniques. The distinct fluorescent emission characteristics of these polymorphs demonstrated morphology-related optical waveguiding features. Specifically, the plate-type Form A1 emitted light with a 2D blue hue, while the needle-type Form A2 emitted light with a yellowish-green colour. Additionally, the impressive waveguiding capabilities of Form B1 were explored in both straight and singly/doubly bending configurations to facilitate fluorescence propagation. Consequently, there is significant interest in developing organic materials based on GFP chromophores, which exhibit low emission in solution but display multi-fluorescent emission in the solid state. These materials are promising for applications such as optoelectronic devices, security tags, live cell imaging, and fluorescent inks. Polymorphs of GFPc analogs A and B display differences in their optical waveguiding properties in 1D and 2D depending on the crystal shapes. Furthermore, Form B1 demonstrates efficient optical waveguiding capabilities even when the crystal is bent.

Synthesis and concomitant polymorphs of green fluorescence protein chromophore-anthracene-based fluorescent analogue - Mali, Bhupendra P.; Dabke, Niteen B.; Dash, Soumya R.; Biswas, Anupam; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Crystal Growth & Design, 2025)
Controlled variations in fluorescence properties hold significant promise for applications in optical sensors, bioimaging, and advanced display devices. However, constructing multicolor fluorescent systems remains a challenge. In this study, we demonstrate the development of multicolor fluorescence by generating polymorphs of a novel green fluorescent protein chromophore analogue, which exhibits distinct photoluminescence emissions in the solid state. The observed emission variations are attributed to differences in molecular conformation due to variations in pi-stacking interactions between the polymorphs. This offers a novel approach to designing materials with tunable fluorescence properties.

Switchable solid-state emission in GFP chromophore analogue cocrystals via competing AIE and ACQ pathways - Mali, Bhupendra P.; Dabke, Niteen B.; Sharma, Himanshu; Dash, Soumya Ranjan; Manoj, Kochunnoonny; Vanka, Kumar; Gonnade, Rajesh G. (CrystEngComm, 2026)
We present a crystal-engineering approach enabling switchable solid-state emission (green -> orange -> quenched) in GFP-chromophore analogue cocrystals. The coformer's electronic and supramolecular effect shifts the photophysical pathway: intramolecular CT in cocrystal-I (green) and cocrystal-III (quenched) and intermolecular CT in cocrystal-II, yielding orange emissions and highlighting cocrystallization's power for tunable luminophores.